Linking Learning Styles and Learning on Mobile Facebook - Chen, Yu-ching (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
With continued development of related technologies, Web 2.0 has become an important site of learning innovation. In particular, social networking sites such as Facebook, which have become popular, have the potential to function as an educational tool enabling peer feedback, interaction, and learning in a social context. Preparing appropriate environments for learners with different needs is essential to learning in general and online learning in particular. Yet, in order to create such learning environments, educators must understand differences in students’ learning styles. Although some research focuses on the effects of individual differences such as age and gender on the use of social networking sites, experimental research related to students’ learning styles is still limited. This study used Kolb’s Learning Style Model to investigate differences in student learning outcomes and satisfaction using mobile Facebook for learning, according to learning style. Results showed that participants with “Assimilating” and “Diverging” learning styles performed better than those with “Accomodating” and “Converging” learning styles did and had higher self-efficacy, observational modelling and habit strength toward learning in mobile Facebook. The paper also makes suggestions for integrating mobile Facebook into class and recommendations for future research.